PERBANDINGAN BUSI IRIDIUM dan BUSI STANDAR terhadap DAYA SEPEDA MOTOR SCOOPY 110 cc TAHUN 2023: COMPARISON OF IRIDIUM SPARK PLUG AND STANDARD POWER PLUG 110 cc SCOOPY MOTORCYCLE IN 2023 - Maulana Azkiya; Margianto; Nur Robbi (RING ME, 2023)
The ignition system is an important component in a gasoline engine that ensures motor operation.Its function is to produce a spark using an ignition coil, which is then channeled to the spark plugvia a high-strength cable to burn the fuel mixture that has been compressed in the cylinder. Thisstudy used a dynamometer to test engine performance with varying RPM (4000, 6000, and 8000)in each trial 3 times. The research results show that the use of iridium spark plugs on the 2023Scoopy 110 cc motorbike results in an increase in engine power. More wear-resistant iridiumelectrodes provide a stronger and more stable spark, optimize fuel combustion and increaseoverall engine power. Combustion efficiency, especially fuel consumption, is also increased by theuse of iridium spark plugs. Thin iridium electrodes provide a stronger and more stable sparkthereby increasing the efficiency of fuel combustion in the combustion chamber. These findingsconfirm that the use of iridium spark plugs brings significant benefits in terms of increasing enginepower, responsiveness, fuel consumption and vehicle engine reliability. Therefore, it isrecommended to consider the use of iridium spark plugs as an effective and efficient option toimprove vehicle performance.